Identification of Vulnerable Lines in Transmission Network for Cascading Failure Based on PageRank Algorithm - Mingkui WEI; Quan ZHOU; Yuyan SONG; Yuhong WANG; Hong ZHOU; Shaorong CAI; Li JIANG (Zhongguo dianli)
In order to quickly and accurately identify the vulnerable lines that may trigger cascading failure in the power grid, a double-layer method for identifying vulnerable lines in the transmission network was proposed based on PageRank algorithm, which takes into account the cascading effect of faults. Firstly, the time series network model of transmission network is established based on the snapshot method with consideration of the evolution process of the cascading failure. Then, regarding the interaction of transmission lines and the immunity of lines to load fluctuation, a shallow identification model based on extended PageRank algorithm is constructed to calculate the vulnerability of transmission lines. Finally, the algorithm reconstruction is used to show the relationship between failures and the deep identification model of vulnerable lines is established to comprehensively analyze the vulnerability of lines. The change process of vulnerability in the cascading failure can be described at the same time. A case study was carried out on IEEE 39 bus system to demonstrate the rationality and accuracy of the suggested method.